A Teoria dos Campos Conceituais num Processo de Formação Continuada de Professores - Santana, Eurivalda; Alves, Alex Andrade; Nunes, Célia Barros [UNESP] (FapUNIFESP (SciELO), 2015)
The Theory of Conceptual Fields aims to provide frame and some principles for the study of development and learning of students' complex skills. Comprehending the learning as a process levered by actions accomplished in teaching, we use this theory in the development of research activities inserted in processes and practices of teaching. Thus, this article aims to analyze the teacher's reflections regarding the application of the Theory of Conceptual Fields during a process of continuous learning that focused on the work with concepts of Additive Structures in the early years. It is a cutout of a bigger research that had as main objective to develop a collaborative teacher education between early years teachers and researchers in a collaborative perspective. To realize the proposed objective, the final report was analyzed and answered by four of the participating teachers in the education process. The analysis of the reflections made by the teachers in the final report shows that, for them, the application of this theory during the education process provided reflections on the way to develop the teaching process, as well as, to give support for the construction activities that offer meaning to mathematical operation, consenting to understanding the relationships involved in these concepts.
The theory of conceptual fields in a continuous teacher education process
Keywords: Collaborative practice; Teacher education; Theory of Conceptual Fields